Microencapsulation for controlled drug delivery: a comprehensive review - Gupta, AK; Dey, BK (Sunsari Technical College Journal, 2013)
Microencapsulation is described as a process of enclosing micron sized particles of solids or droplets of liquids or gasses in an inert shell, which in turn isolates and protects them from the external environment as well as control the drug release profile. Microencapsulated particle is having diameter between 3 [-] 800µm which differ them from other technologies such as nanotechnology and macroparticle in their morphology and internal structure. This review paper will address the background of microencapsulation technology, commonly used microencapsulation methods with its advantages and disadvantages and its applications in pharmaceutical field. This article also gives an overview on the general aspects and recent advances in drug-loaded microparticles to improve the efficiency of various medical treatments. The review paper will also address about the other factors affecting microencapsulation and its limitation. The article will also discuss about various findings described in the published scientific journals and patent literatures. Based on the existing results and authors’ reflection, this review gives rise to reasoning and suggested choices of process parameters and microencapsulation procedure. DOI: http://dx.doi.org/10.3126/stcj.v1i1.8660 Sunsari Technical College Journal Vol.1(1) 2012 48-54